Analisis Kesehatan Laporan Keuangan pada PT Bank Muamalat Indonesia Tbk dengan Menggunakan Metode Camel Tahun 2015–2019 - Pratikto, Muhammad Iqbal Surya; Fabrela, Clarissa Belinda; Basya, Maziyah Mazza (Program Studi Ilmu Ekonomi UIN Sunan Ampel Surabaya, 2021)
The purpose of this study is to determine the level of health at PT Bank Muamalat Indonesia Tbk using the CAMEL method (Capital, Asset Quality, Management, Earning, and Liquidity) for the 2015-2019 period. The results of research on the health of PT Bank Muamalat Indonesia Tbk in 2015-2019 show that the ratio of CAR, NPF, and NI is considered good, while the ratio of PDN and FDR is considered quite good. However, the ROA, ROE, and BOPO ratios are considered less good because all the results of the ratios are included in the unhealthy category.